Trends in Canadian Newspaper Coverage of International News, 1988-2000: Editors' Assessments - Soderlund, Walter C. and Lee, Martha F. and Gecelovsky, Paul (Canadian Journal of Communication, 2002)
Between 1988 and 2000, a series of comprehensive surveys were administered to the editors of Canada's daily newspapers, in order to obtain their views concerning Canadian news reportage of international events. The 1995 data demonstrated an editorial perception of a marked decline in the quality and quantity of international news coverage. The 2000 data pointed to a partial recovery. Canadian editors, however, remain convinced that it is only in local news reporting that newspapers have a comparative advantage over other mass media. This study acknowledges the reversal that may have occurred following the events of September 11, 2001; the series will resume with the aim of charting editorial perceptions following those events.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjIwMDJ2MjduMWExMjcz